European Court of Human Rights Case Law on Genetic Information in the Scope of International Biomedical Law - Kwiatkowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The aim of the study is to analyze the case law of the European Court of Human Rights on genetic information in the scope of international biomedical law, as expressed in the International Declaration on Human Genetic Data and the Convention on the Protection of Human Rights and Human Dignity in the Field of Application of Biology and Medicine. The Court held that the genetic information is protected under the law of the Convention on Human Rights and Fundamental Freedoms. The model of the right to respect for private life is reflected in its shape, as the Court noted in the Van der Velden v. The Netherlands and S. and Marper v. The United Kingdom cases. It leads to the conclusion that the provision of Article 8 of the Convention provides the protection of genetic information, subject to certain restrictions that are “in accordance with law” and “necessary in a democratic society”. Such conclusion is in compliance with art. 12, art. 17 (b) art. 21 (c) of the International Declaration on Human Genetic Data, and art. 11 of the Convention for the Protection of Human Rights and Dignity of the Human Being with regard to the Application of Biology and Medicine.